2018
DOI: 10.7567/jjap.57.08rb14
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and evaluation of ultra-long carrier lifetime Czochralski silicon

Abstract: Impact of the ultralow-carbon concentration of below 1 ' 10 15 atoms/cm 3 and thermal history on the bulk lifetime of phosphorus (P)-doped magnetic-field-applied Czochralski (MCZ) silicon was investigated. In order to accurately measure the long bulk lifetime, a direct-current photoconductive decay method was applied to a rectangular sample with a sectional area larger than 400 mm 2 . The measurement of an ultralong bulk lifetime of longer than 20 ms was demonstrated using the P-doped MCZ silicon with a carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…1,2) Large-diameter magnetic-field applied Czochralski (MCZ) crystals are advantageous from the viewpoint of productivity in comparison with floatingzone (FZ) crystals. [3][4][5][6][7] MCZ crystals contain more than an order of higher O impurities than FZ crystals. A small amount of residual C impurities behave as nucleation sites for oxygen precipitates which act as recombination centers reducing the carrier lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Large-diameter magnetic-field applied Czochralski (MCZ) crystals are advantageous from the viewpoint of productivity in comparison with floatingzone (FZ) crystals. [3][4][5][6][7] MCZ crystals contain more than an order of higher O impurities than FZ crystals. A small amount of residual C impurities behave as nucleation sites for oxygen precipitates which act as recombination centers reducing the carrier lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Because it is difficult to manufacture 300 mm silicon wafers by the FZ method, the growth technique for Czochralski silicon (Cz-Si) single crystals by which the wafer diameter can be easily increased compared with that for FZ-Si crystals should be developed. [8][9][10] Nevertheless, the incorporation of oxygen atoms at concentrations of 10 17 cm À3 from the melt of silicon in a silica crucible during Cz-Si crystal growth is unavoidable, resulting in the generation of oxide precipitates and thermal donors. Although the generation can be suppressed by lowering [Oi], it will not be compatible with asgrown defect-free crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, a shift to 300 mm silicon wafers has been promoted in Europe to reduce a device manufacturing cost . Because it is difficult to manufacture 300 mm silicon wafers by the FZ method, the growth technique for Czochralski silicon (Cz‐Si) single crystals by which the wafer diameter can be easily increased compared with that for FZ‐Si crystals should be developed . Nevertheless, the incorporation of oxygen atoms at concentrations of 10 17 cm −3 from the melt of silicon in a silica crucible during Cz‐Si crystal growth is unavoidable, resulting in the generation of oxide precipitates and thermal donors.…”
Section: Introductionmentioning
confidence: 99%
“…As for the DC-PCD method, we reported that there is a strong correlation between the carbon concentration and the bulk lifetime of phosphorus (P)-doped MCZ silicon using the DC-PCD method in our previous paper. 18) Although the bulk lifetime of the low-carbon content crystal was relatively long (exceeding 20 ms), the bulk lifetime measurement using the DC-PCD method above 20 ms is not assumed in the JIS standard. 19) However, based on the principle of the DC-PCD method, the bulk lifetime above 20 ms can be measured using a sample sufficiently larger than the carrier diffusion length to prevent surface recombination.…”
mentioning
confidence: 99%
“…To prepare samples with different bulk lifetimes, four 8 inch P-doped MCZ silicon ingots (Crystal A-D) were grown by controlling the carbon concentration and thermal history during crystal growth. 18) Several types of rectangularshaped samples with different dimensions cut from these MCZ silicon ingots were used. The oxygen concentrations of these samples were approximately 5.0 × 10 17 atoms cm −3 (Old ASTM), while the carbon concentrations changed from 1.2 × 10 14 to 7.3 × 10 14 atoms cm −3 , as measured by the photoluminescence method.…”
mentioning
confidence: 99%